Rapid and efficient maximum power point tracking in photovoltaic systems with modified fuzzy logic approach - Said, El-bot; Moujahid, Yassine El; Mohamed, Chafik El Idrissi; Benlafkih, Abdessamad (Institute of Advanced Engineering and Science, 2025)
Photovoltaic systems (PVs) often face difficulties in maximizing their output power and maintaining a stable DC-DC connection voltage, especially under variable weather conditions (VWC). The power produced by photovoltaic panels is very sensitive to changes in sunlight and temperature, which vary throughout the day. This paper presents the design of an intelligent controller approach based on modified fuzzy logic (MFLC), adapted to enable the most effective maximum power point tracking (MPPT) of a photovoltaic solar module. The technique reduces delays in MPPT and sustains efficiency despite changing environmental conditions. A DC-DC boost converter is connected to the photovoltaic solar module, which in turn is linked to a load, and computer simulations using MATLAB/Simulink were used to validate the method's effectiveness. Results reveal that the MFLC controller significantly enhances the efficiency of the PVs, achieving improvements of up to 97.05%, with a rapid settling time of less than 10 milliseconds across all test scenarios.